Experimental Study of Soil Resistivity Using Different Rod Design and Material for Grounding System - Mahadi, M.A.A; Othman , N. A.; Jamail, N.A.M.; Adzis, Z. (Evolution in Electrical and Electronic Engineering, 2020)
Grounding system is the most crucial area in power system network. Poor grounding system can be dangerous to the users and wire of the electrical distribution system in the event of electrical fault. To prevent this accident, it is very important to have a good grounding system to protect the system as well as to the user. Therefore, this paper measures the soil resistivity with various planted electrode designs using Wenner Four Point method with the help of equipment earth testers. The experimental works was conducted in clay soil type using copper and iron rod materials. The experimental results show that the new rod design with branches can be considered not suitable to replace the standard rod since the measured soil resistivity was much higher. It is also proven that the copper rod exhibits better value of soil resistivity which can be used for the grounding system.